2013
DOI: 10.1177/1753944713481512
|View full text |Cite
|
Sign up to set email alerts
|

A heat and moisture mask attenuates cardiovascular stress during cold air exposure

Abstract: Subgroup analyses suggested that the effect of the HME in mitigating systolic blood pressure increase from inhalation of cold air was significantly greater for patients aged 60 years or over than for those under 60 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…During cold exposure, we detected an increase of systolic and diastolic blood pressure of approximately 30 and 20 mm Hg in hypertensive subjects. The magnitude of the BP responses is comparable [13, 14] or higher [15] to that seen in previous studies with similar cold exposure in healthy subjects and hypertensive patients with preserved kidney function. It has been well documented that the cold-induced acute rise of BP is primarily caused by the activation of the autonomic nervous system.…”
Section: Discussionsupporting
confidence: 77%
“…During cold exposure, we detected an increase of systolic and diastolic blood pressure of approximately 30 and 20 mm Hg in hypertensive subjects. The magnitude of the BP responses is comparable [13, 14] or higher [15] to that seen in previous studies with similar cold exposure in healthy subjects and hypertensive patients with preserved kidney function. It has been well documented that the cold-induced acute rise of BP is primarily caused by the activation of the autonomic nervous system.…”
Section: Discussionsupporting
confidence: 77%
“…The use of a protective mask with a heating and humidifying properties mitigated the increase in BP especially among ageing hypertensive subjects (above 60 yrs.) [62]. An earlier study with healthy subjects showed similarly that proper head protection reduces cold-related increase in BP [77].…”
Section: Hypertensionmentioning
confidence: 93%
“…A large share of these have used the cold pressor test for cardiovascular stimulation [40,51,55,[57][58][59][60]. The reminder of the research included whole-body (with or without facial exposure) skin cooling [38,42,43,[61][62][63][64][65], local cooling of skin [66] or face [36], cold water immersion in association with sauna bathing [67], or brief intense whole-body cold exposures (cryostimulation) [68,69]. In the majority, but not all [36,40,62,63,65,70] of the studies cardiovascular responses were compared with healthy controls.…”
Section: Cardiovascular Responses and Cold Exposure In Persons With Cmentioning
confidence: 99%
“…Randomized cross-over trials conducted in Chinese cities of Beijing and Shanghai have also reported reduction of blood pressure and increased heart rate variability parameters from wearing a disposable respirator for 48 h [53] or for a few hours while walking [54,55], as a likely result of reduced exposure to ambient particulate concentrations. However, inhalation of cold, dry air can also increase blood pressure, enhancing the risk of myocardial infarction, particularly among individuals affected by pre-existing hypertensive cardiovascular disorders [56]. Therefore, considering the influence of cold air on systolic blood pressure, the use of facemasks against COVID-19 may also mitigate the effect of hypertension on the risk of myocardial ischemia, particularly in people with pre-existing hypertensive cardiovascular disease [56].…”
Section: Sars-cov-2 Air Pollution Blood Pressure and Face Masksmentioning
confidence: 99%
“…However, inhalation of cold, dry air can also increase blood pressure, enhancing the risk of myocardial infarction, particularly among individuals affected by pre-existing hypertensive cardiovascular disorders [56]. Therefore, considering the influence of cold air on systolic blood pressure, the use of facemasks against COVID-19 may also mitigate the effect of hypertension on the risk of myocardial ischemia, particularly in people with pre-existing hypertensive cardiovascular disease [56].…”
Section: Sars-cov-2 Air Pollution Blood Pressure and Face Masksmentioning
confidence: 99%